HUBUNGAN TINGKAT PENGETAHUAN, KEPATUHAN TERHADAP SAFETY, REWARD PUNISHMENT PEKERJA KONSTRUKSI DENGAN KESIAPSIAGAAN KEBAKARAN di PROYEK APARTEMEN X SEMARANG - Mudrika, Mudrika; Suroto, Suroto; Lestantyo, Daru (Jurnal Ilmiah Mahasiswa, 2020)
Preparedness activities take place before an emergency accurs with the aim of devolopment of operational capacity when an emergency occurs. Apartment building contruction as a place to work must assure its safety and securty or the workers. A large number have variaty activities such as use of electric tools so they have a high risk and fire risk increase. The purpose of this study was to analyze correlation between knowladge,compliance with safety, reward punishment with the prepsredness of employees in the apartment project Semarang. The type of research is quantitative with cross sectional approach. The population in this study as many as 203 people. The sample used in this study was 70 people with simple random sampling technique. Data was taken using a research questionnaire. Based on result of research by using chi-square testobtained variabel associated with employee preparedness fire risk increase is complience with safety (p value = 0,022). While the variables that are not related with fire preparedness are knowladge (p value = 0,504), reward (p value = 0,117), punishment (p value = 0,967). Researchers suggest providing information on fire preparedness, and carrying out more stringent supervision of any work procesess that have potential to cause fires.